The grudge - Shimizu, Takashi, 1972-; Gellar, Sarah Michelle, 1977-; Behr, Jason, 1973-; Mapother, William, 1965-; Du Vall, Clea.; Strickland, KaDee, 1977-; Ettlin, Lukas; Yamamoto, Hideo, 1960-; Young, Christopher, 1957-; Shimizu, Takashi, 1972-; Columbia TriStar Home Entertainment (Firm) (Culver City, Calif. : Columbia TriStar Home Entertainment, 2005)
Karen is an American nurse living and working in Tokyo who agrees to cover the shift of another nurse. When she enters the assigned home, she discovers an elderly woman who is lost in a catatonic state. As she tends the woman, Karen hears scratching sounds upstairs and goes to investigate. Within this house is a chain of terror more terrifying than she could ever imagine, resulting from a terrifying evil that was born years before. As more people die, Karen is pulled into the cycle of horror and learns the secret of the vengeful curse. Now she must stop it before it's too late.
Title from container.
Widescreen.
Originally released as a motion picture in 2004.
Based on the film "Ju-on: the grudge" by Takashi Shimizu.
Special features: "A powerful rage: behind 'The grudge'": a five part making-of documentary; cast and crew commentary including Sam Raimi, Ted Raimi, Sarah Michelle Gellar and others; "Under the skin" featurette: explores the medical explanation of the fear response in film; previews.
Directors of photography, Lukas Ettlin, Hideo Yamamoto ; editor, Jeff Betancourt ; music, Christopher Young.
Keywords: Spirits -- Drama; Revenge -- Drama; Violent deaths -- Drama; Feature films; Films for the hearing impaired; Horror films